Long Non-coding RNA LRNA9884 Promotes Acute Kidney Injury via Regulating NF-kB-Mediated Transcriptional Activation of MIF - Zhang, Yingying; Tang, Patrick Ming-Kuen; Niu, Yangyang; García Córdoba, Cristina Alexandra; Huang, Xiao-Ru; Yu, Chen; Lan, Hui-Yao (Frontiers in Physiology, 2020)
Acute kidney injury (AKI) is one of the most common complications affecting hospitalized patients associated with an extremely high mortality rate. However, the underlying pathogenesis of AKI remains unclear that largely limits its effective management in clinic. Increasing evidence demonstrated the importance of long non-coding RNAs (lncRNAs) in the pathogenesis of AKI, because of their regulatory roles in transcription, translation, chromatin modification, and cellular organization. Here, we reported a new role of LRNA9884, a Smad3-dependent renal lncRNA, in AKI. Using experimental cisplatin-induced AKI model, we found that LRNA9884 was markedly up-regulated in the nucleus of renal tubular epithelium in mice with AKI. We found that silencing of LRNA9884 effectively inhibited the production of inflammatory cytokines MCP-1, IL-6 and TNF-α in the mouse renal tubular epithelial cells (mTECs) under IL-1β stimulation in vitro. Mechanistically, LRNA9884 was involved into NF-κB-mediated inflammatory cytokines production especially on macrophage migration inhibitory factor (MIF). Collectedly, our study suggested LRNA9884 promoted MIF-triggered the production of inflammatory cytokines via NF-κB pathway after AKI injury. This study uncovered LRNA9884 has an adverse impact in AKI, and targeting LRNA9884 might represent a potential therapeutic target for AKI.